Sequence Variation in the Bovine Lipin-1 Gene (LPIN1) and Its Association with Milk Fat and Protein Contents in New Zealand Holstein-Friesian × Jersey (HF × J)-cross Dairy Cows - Xiaohua Du (MDPI AG, 2021)
Lipin-1 is known to play a regulatory role in tissues that function in lipid metabolism. In dairy cows, the lipin-1 gene (LPIN1) is highly expressed in the mammary gland, but its function in milk production is less understood. In this study, we used PCR-single strand conformation polymorphism analysis to investigate sequence variation in three regions of bovine LPIN1 in New Zealand Holstein-Friesian × Jersey (HF × J)-cross dairy cows, including part of the 5′ non-coding region, the region containing the LPIN1β-spliced exon, and the sixth coding exon that encodes the putative transcriptional activating domain of the protein. No variation was found in the LPIN1β-spliced exon, but two sequence variants containing one single nucleotide polymorphism (SNP) were identified in the 5′ non-coding region and four sequence variants containing four non-synonymous SNPs were identified in the sixth coding exon. Among the three common variants of the sixth coding exon, variant C was found to be associated with an increase in milk fat percentage (presence 4.96 ± 0.034% vs. absence 4.81 ± 0.050%; p = 0.006) and milk protein percentage (presence 4.09 ± 0.017% vs. absence 3.99 ± 0.025%; p = 0.001), but no associations (p > 0.01) were detected for milk yield. These results suggest that variation in LPIN1 affect the synthesis of fat and proteins in milk and has potential as a gene-marker to improve milk production traits.